The effect of hand-eye coordination, flexibility, and confidence training on Forehand serve accuracy in beginner tennis athletes Club table Softlyi Padang Panjang - Azaria Elvira; Bafirman HB; Ishak Aziz; Aldo Naza Putra; Fiky Zarya (Jorpres (Jurnal Olahraga Prestasi), 2023)
The purpose of the study was to determine the effect of hand-eye coordination training, flexibility and confidence on the accuracy of forehand serve in novice table tennis athletes of the Padang Panjang soft club. The type of research is quantitative. The population of novice table tennis Club Softlyi Padang Panjang athletes aged 12–15 years is 16 people. Total sampling technique. Confident data collection techniques using questionnaires and forehand service accuracy tests using forehand service accuracy. Data analysis using a two-way ANOVA test. The results of the analysis found that overall there was no difference in the accuracy of forehand service of the hand coordination training model with flexibility, judging from the average value of hand-eye coordination training (19.50) not much different from the average value of the flex model (18.25) and in the calculation of two-lane ANAVA there was no significant difference due to Sig. 1.00 0.05. There is no interaction between the training model and confidence in physical fitness can be seen from Sig. 0.834 0.05. Forehand service accuracy The flex model treatment was better than the hand-eye coordination model in the high-confidence group. The results of the analysis found that overall there was no difference in the accuracy of forehand service of the hand coordination training model with flexibility, judging from the average value of hand-eye coordination training (19.50) not much different from the average value of the flex model (18.25) and in the calculation of two-lane ANAVA there was no significant difference due to Sig. 1.00 0.05. There is no interaction between the training model and confidence in physical fitness can be seen from Sig. 0.834 0.05. Forehand service accuracy The flex model treatment was better than the hand-eye coordination model in the high-confidence group.